2022
DOI: 10.1128/spectrum.01056-22
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Inhibitors Reduce SARS-CoV-2 Replication in Cultured Cells

Abstract: There is an urgent need for effective therapeutic drugs to control the pandemic caused by severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2). We found that several inhibitors of protein kinases C (PKCs) dramatically decrease the replication of SARS-CoV-2 in cultured cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Additionally, the presence of PKCα/β is essential for IBV or N protein-mediated suppression of antiviral gene expression (Fig 9F and Fig 11F) and facilitates IBV infection (Fig 9 D-E). In line with our findings, a recent study has demonstrated that the replication of SARS-CoV-2 is impeded by pan-PKC inhibitors such as Go 6983, Bisindolmaleimide I, Enzastaurin, and Sotrastaurin [75]. This suggests that PKC may play an essential role in facilitating coronavirus infection.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the presence of PKCα/β is essential for IBV or N protein-mediated suppression of antiviral gene expression (Fig 9F and Fig 11F) and facilitates IBV infection (Fig 9 D-E). In line with our findings, a recent study has demonstrated that the replication of SARS-CoV-2 is impeded by pan-PKC inhibitors such as Go 6983, Bisindolmaleimide I, Enzastaurin, and Sotrastaurin [75]. This suggests that PKC may play an essential role in facilitating coronavirus infection.…”
Section: Discussionsupporting
confidence: 91%
“…Because many polymorphisms in various PKC genes have been identified and because drugs targeting PKC are under investigation in clinical trials for cancer and other diseases ( Callender et al, 2018 ; Kawano et al, 2021 ; Ma et al, 2010 ), future research should explore whether PKC regulation impacts human susceptibility and the severity of SARS-CoV-2 infection. A recent study reported that PKC inhibitors block the replication of ancestral SARS-CoV-2 on A459/ACE2 expressing cells ( Huang et al, 2022 ). The biological effects of PKC are wide-ranging, and even though most PKC isoenzymes are ubiquitous and many cells can co-express different PKC isoforms, some of them are expressed in a tissue-specific manner ( Blázquez and Saiz, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study revealed that bisindolylmaleimide IX, a PKC inhibitor, targets the viral protease 3CLpro 57 . Another study found that several inhibitors of protein kinases C (PKCs) including enzastaurin decrease the replication of SARS-CoV-2 in cultured cells 58 . The evidence above indicates that enzastaurin is a potential therapeutic agent against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%